Cytotoxic effect of green tea leaf extract on tumor cell line - Ahmed, Manhal F. (The Iraqi Journal of Veterinary Medicine, 2017)
The study was conducted to evaluate antitumor effects of green tea (Camellia sinensis) extracts (aqueous and methanolic) on Rhabdomyosarcoma; cell line and a normal cell line; mouse embryo fibroblast; Chemical detections of green tea extracts revealed that the aqueous and methanolic extracts were positive for flavonoids, alkaloids, phenol and glycosides. The percentage growth inhibition of five plant concentrations (50, 100, 250, 500 and 1000 µg/ml) were assessed in vitro using tumor cell lines Rhabdomyosarcoma and normal cell line mouse embryonic fibroblasts. The results revealed that the five concentrations of the plant extracts showed anti-tumor properties in a concentration-dependent manner, and the methanolic extract recorded better values of percentage growth inhibition than the aqueous extract in Rhabdomyosarcoma cell lines, while, less percentage growth inhibition values were recorded in the mouse embryo fibroblast cell line.